Wideband vibration isolation and energy harvesting based on a coupled piezoelectric-electromagnetic structure. (1st February 2023) - Zhang, Yongqi; Yang, Tao; Du, Houfan; Zhou, Shengxi
Highlights: A dual-purpose coupled piezoelectric-electromagnetic structure (DCPES) is proposed. The electromagnetic element mutually complements with piezoelectric elements. The dynamic model of the DCPES is established and verified by experiments. The DCPES harvests energy at low frequencies and isolates vibration above 13 Hz. Abstract: This paper proposes a dual-purpose coupled piezoelectric-electromagnetic structure (DCPES) for wideband vibration isolation and energy harvesting. It includes two piezoelectric elements and one electromagnetic element, which are used to harvest energy from low-level and low-frequency vibrations and isolate some undesired vibrations. These two combinations result in low resonant frequencies and available nonlinearity. The electromagnetic element mutually complements with piezoelectric elements, and has positive stiffness and hard nonlinearity to damp vibrations with an isolated mass platform. The corresponding dynamic model of the DCPES is established, and the response displacement and output voltage are predicted numerically. In addition, the effects of excitation amplitude, the magnetic constant of the magnet, geometric parameters of the piezoelectric beam, and equivalent mass of the mass platform on displacement transmissibility and output response are explored. More importantly, experimental tests are performed to verify the design and numerical analysis. It is found that the DCPES can efficiently convert vibration energy into electrical energy in a wide frequency range of 5–13 Hz, and successfully dampens oscillations in the frequency range above 13 Hz (the displacement transmissibility is less than 1). The peak output power of the electromagnetic element is up to 15.2 mW, and the total peak output power of two piezoelectric elements reaches 4.6 mW under the excitation amplitude of 0.8 g (g = 9.8 m/s 2 ). Case studies of parameters show that simultaneous wider bandwidth, higher output response, and vibration isolation can be achieved by changing the parameters of the DCPES.